Why sp2‐like nanosilicons should not form: Insight from quantum chemistry. Issue 4 (29th March 2012) - Sheka, E. F.; Nakai, Hiromi; Yoshizawa, Kazunari; Ando, Koji; Nakajima, Takahito; Brändas, Erkki J.
Abstract The odd‐electron molecular theory, which takes into account the electron correlation, has been applied for a comparative consideration of sp2 nanocarbons and their siliceous analogues. Four characteristic quantities that involve the energy misalignment, the number of effectively unpaired electrons, the squared spin value, and CC and SiSi chemical bond lengths have been suggested to classify the extent of the odd electron correlation in both families. Providing a considerable enlargement of the internuclear distances, the electron correlation in siliceous species is extremely strong thus resulting in complete radicalization of the species and proving the impossibility of their existence at ambient conditions in contrast to carboneous ones that are not so strong correlated. © 2012 Wiley Periodicals, Inc.